Development questions for 25 years - Lance Taylor (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Recent growth experience in developing countries is reviewed, with an emphasis on structural change and sources of effective demand. How policy influences such outcomes is analyzed in light of historical experience. Options are discussed for macro and industrial/commercial policy, and how they may influence the growth process. The recent `institutional turn' in development theory may obfuscate serious policy analysis. – development ; growth ; economic policy ; institutions
Keywords: O2; O4; 330; Entwicklung; Wirtschaftswachstum; Wirtschaftspolitik